APLIKASI PENJUALAN FURNITUR MENGGUNAKAN MARKERLESS AUGMENTED REALITY DENGAN FLUTTER - Naufal Nur Faiq; Erik Iman Heri Ujianto (LPPM Universitas Abdurrab, 2026)
The rapid expansion of e-commerce has transformed consumer purchasing behavior from physical stores to digital platforms. In the furniture category, limited product visualization often leads to discrepancies between customer expectations and the actual products received. This study aims to develop a markerless Augmented Reality (AR)-based furniture sales application using the Flutter framework and ar_flutter_plugin to support in-situ product visualization. The research adopts a prototyping approach consisting of literature review, system requirement analysis, user interface design, application implementation, and evaluation through functional testing and usability assessment. The developed application enables real-time visualization of 3D furniture models without physical markers and provides button-based controls for object manipulation. Experimental results indicate that the system can render 3D objects stably under various lighting conditions and operate smoothly across multiple Android devices. These findings suggest that Flutter-based AR applications have the potential to enhance users’ understanding of furniture products in online shopping environments.